Metric Dimensions and Partition Dimensions of a Multiple Fan Graph - Restina Silalahi; Mulyono (PT FORMOSA CENDEKIA GLOBAL, 2023)
The metric dimension is a distinguishing set with minimum cardinality, while the partition dimension is a distinguishing set with cardinality. The purpose of this study is to find the metric and partition dimensions of a double fan graph which is the result of the join operation of the complete graph and the path graph. The results obtained from this study are the metric dimensions , partition dimensions.